Measurement analysis of strata deformation caused by construction of quasi-rectangular shield - Shi-ju Ma; Kai-rong Hong; Yong-gang Ding; Ming-ming Cao; Tian-jing Guo; Xin-zhuang Lou (Scientific Reports)
Abstract This paper is based on a large cross-section quasi-rectangular shield tunnel project on Zhengzhou Metro Line 8, where field excavation tests were conducted to study the ground deformation patterns induced by quasi-rectangular shield tunneling through in-situ monitoring. The research results demonstrate that surface settlement can be divided into three distinct phases according to the spatial relationship between the shield cutterhead and monitoring sections: a slow uplift period, a rapid settlement period, and a gentle settlement period. Similarly, the stratified ground settlement is also influenced by the spatial position relationship between the shield and monitoring points, with the primary stratified settlement occurring after the shield machine moves away from the shield tail. The transverse settlement trough distribution of the ground surface tends to be symmetrical and approximately follows the Peck curve distribution.